Sustainable Energy Technologies - Hanjalić, Kemo (Springer, 2017)
This book provides an up-to-date review of the status and prospects of different options in energy conversion and storage technologies, as seen by a panel of world leading experts. It offers a platform for readers engaged in planning and undertaking new energy solutions or retrofitting and redesigning the existing installations to confront and to compare the pros and cons of various novel technology options. Contributing articles cover new clean and zero-emission coal technologies, solar, wind, nuclear, fuel cells, hydrogen and hybrid technologies, accompanied by treatises on the challenge of increasing global energy needs and consumption, issues of sustainability, and on specific ideas for efficient production and use of energy based on modern rationing technologies.